(untitled) (Texas Journal of Medical Science, 2023)
Bronchiectasis is characterized by a constant and abnormal expansion of the airways of the lungs (bronchi) and/or a violation of the tone of the muscle layer of the bronchial wall due to inflammation, sclerosis, dystrophy, hypoplasia. Bronchiectasis is a very common disease that is the main cause of respiratory problems. A deficiency in the host’s immune response to bacterial infection is considered to be the main condition for the development of bronchiectasis. In addition, many patients have no identifiable cause and are defined as having an idiopathic disease. This can lead to the development of a chronic respiratory tract infection and subsequent inflammation. Patients tend to have persistent disease despite aggressive use of antibiotics and optimal sputum clearance techniques. New therapies based on the manipulation of the immune response are becoming available and offer significant promise for the treatment of this condition